Right stellate ganglion block improves learning and memory dysfunction and hippocampal injury in rats with sleep deprivation - Dongsheng Dai (BMC, 2021)
Abstract Background Sleep deprivation (SD) often leads to complex detrimental consequences, though the mechanisms underlying these dysfunctional effects remain largely unknown. We investigated whether the right stellate ganglion block in rats can improve the spatial learning and memory dysfunction induced by sleep deprivation by alleviating the damage of hippocampus in rats. Methods Sixty four male Sprague Dawley rats were randomly divided into four groups: Control, SD (sleep deprivation), SGB (stellate ganglion block) and SGB + SD (stellate ganglion block+ sleep deprivation) (n = 16). The SGB and SD + SGB groups were subjected to right stellate ganglion block through posterior approach method once per day. SD and SD + SGB groups were treated with modified multi-platform water environment method for 96 h sleep deprivation in rats and their body weights were analyzed. Histopathological changes of hippocampal neurons in rats and the expression of Caspase-3 in hippocampus of rats was detected by western blotting. ELISA was used to detect the content of IL-6, IL-1 in hippocampus and serum melatonin levels. Results Compared with the group SD, the spatial learning and memory function of the group SD + SGB was improved, the weight loss was alleviated, the pathological damage of the hippocampus was reduced and the expression of IL-6, IL-1β and Caspase-3 in the hippocampus was decreased. The content of rat serum melatonin was also increased. Conclusions The right stellate ganglion block can improve the spatial learning and memory dysfunction of rats with sleep deprivation, and the underlying mechanism may be related to alleviating the apoptosis and inflammation of hippocampus of rats with sleep deprivation.